ChinaCALL in retrospect and prospect: opening a welcome window to the World’s CALLs - Gu Yueguo (Journal of China Computer-Assisted Language Learning)
This paper, while sending a welcome message to the world’s CALL communities, presents a historical and developmental review of Chinese practices of educational technologies and ChinaCALL in particular. The review covers topics including the birth and concept of ChinaCALL, ChinaCALL’s pre-CALL heritage, pre-Web ChinaCALL, ChinaCALL in the new millennium, IBOE as a case study of ChinaCALL, and ChinaCALL in prospect. Also discussed are Chinese perceptions of educational technologies occurring at the macro, the meso and ground levels. On the ground level, technology consumers are characterized in terms of pen-pencil conservatives, AV natives, AV-CALL immigrants, CALL natives and CALL standby observers.